Changes in compound flood event frequency in northern and central Europe under climate change - Heinrich, Philipp; Hagemann, Stefan; Weisse, Ralf; Gaslikova, Lidia (Frontiers in Climate, 2023)
The simultaneous occurrence of increased river discharge and high coastal water levels may cause compound flooding. Compound flood events can potentially cause greater damage than the separate occurrence of the underlying extreme events, making them essential for risk assessment. Even though a general increase in the frequency and/or severity of compound flood events is assumed due to climate change, there have been very few studies conducted for larger regions of Europe. Our work, therefore, focuses on the high-resolution analysis of changes in extreme events of coastal water levels, river discharge, and their concurrent appearance at the end of this century in northern and central Europe (2070-2099). For this, we analyse downscaled data sets from two global climate models (GCMs) for the two emissions scenarios RCP2.6 and RCP8.5. First, we compare the historical runs of the downscaled GCMs to historical reconstruction data to investigate if they deliver comparable results for northern and central Europe.Then we study changes in the intensity of extreme events, their number, and the duration of extreme event seasons under climate change. Our analysis shows increases in compound flood events over the whole European domain, mostly due to the rising mean sea level. In some areas, the number of compound flood event days increases by a factor of eight at the end of the current century. This increase is concomitant with an increase in the annual compound flood event season duration. Furthermore, the sea level rise associated with a global warming of 2K will result in double the amounts of compound flood event days for nearly every European river estuary considered.